Direct-access to abdominal ultrasonic investigation from general practice—the role in earlier cancer diagnosis. (24th February 2015) - Ingeman, Mads Lind; Ormstrup, Tina E; Vedsted, Peter
Abstract: Background: Abdominal ultrasound (US) is a safe and low-cost diagnostic tool for various abdominal symptoms. Direct-access to US from general practice has been suggested as a feasible option to promote earlier cancer diagnosis because abdominal cancer often presents with non-specific and vague symptoms, and the exact location may be difficult to identify on the basis of symptoms alone. Objective: To describe patterns of use and cancer prevalence in referred patients when providing Danish GPs with direct-access to hospital-based US. Methods: In an observational study, GPs were given the opportunity to either refer patients directly to US or through a waiting-list at Vejle Regional Hospital in Denmark; 701 patients were included between 1 August 2009 and 31 January 2010. Data were retrieved from the local Radiology Information System, GP referrals and the Danish Cancer Registry. Results: GPs referred 60% of all patients to direct-access US. Cancer was diagnosed in 19 (2.7%) of the referred patients within 6 months after the US investigation. US gave rise to the suspicion of cancer in 11 of these patients (57.9%); 10 of these had been referred to direct-access US. At least one non-malignant diagnosis resulted from US in 59.5% of the cases, while 37.8% of the cases had no final diagnosis. Conclusion: The findings in this study might indicate that GPs refer patients assessed to have a higher risk of cancer through direct-access US. The finding was statistically non-significant, and further research is required to confirm this result.